MINDSET AND PSYCHOLOGICAL ATTRIBUTES FOR LEARNING TO EMPOWER UNIVERSITY STUDENTS’ COMPETITIVENESS - Khairudin, Rozainee (International Journal of Psychosocial Rehabilitation, 2020)
The development of a nation’s economy is dependent on the source of its workforce. In this regard, a recent issue that has become a priority is the employability of university students. Consistent with the Malaysia Education Development Plan (Higher Education), Higher Education Institutions are required to produce competent, holistic and competitive students. To date, findings from studies are inconsistent to determine the main factors that influence university students’ achievements in academic achievement that may lead to their future employability. Following this, the current study explores constructs that are necessary to cultivate university students for success and lead to higher chance of employability. Therefore, the aim of the current study is to examine the relationships between mindset and self-efficacy towards academic achievement and employability. Two sets of survey research were carried out to achieve the purpose of study. Study 1 involved 200 university students from both public and private universities. These respondents completed the Dweck’s Theories of Intelligence Scale and College Self- Efficacy Instrument. Results from study 1 showed a significant difference in growth mindset between public university students and private university students. Results also revealed significant relationships between mindset and academic achievement, as well as between self-efficacy and academic achievement. Furthermore, it was evidenced that mindset and self-efficacy are able to predict students’ academic achievement. In study 2, 137 university students from both public and private universities took part in the study. Mindset was measured using Dweck’s Theories of Intelligence Scale, while employability was measured using the Employability Questionnaire. Results from study 2 showed that there is a significant correlation between growth mindset and employability. Findings from these two studies confirm that mindset, particularly, can be a determiner towards university students’ achievement and employability. The implication that can be deduced from the findings is that higher institutions should focus on individual differences, in this case, improving students’ mindset and self-efficacy to determine high achievement that includes both academic and employability.